Agropastoral Mobility and Rangelands Multiple Uses in the Miombo Frontier Ecozone of Tabora Region, Western Tanzania. (30th October 2017) - Masanja, George Felix
Abstract : This study aimed to examine the argument of environmental resource-use conflict as the primary cause of crop farmers and agropastoralists conflicts in Tabora Region, Tanzania. It explored the multiple interdependent phenomena that affect livelihoods relationships between crop farmers and agropastoralists and the nature of their continuing conflicts over the ecozonal resources. A primary dataset of the two groups' conflicts was used. An ex post facto and multistage sampling design was adopted. A total of 252 respondents were interviewed in three separate villages drawn from agroecological zones fringing the miombo woodland where such tensions are high. Data were analyzed using logistic regression. Results indicate that education ( β = −1.215, .297; p = . 050 ), household size (β = . 958, 2.607; p = . 017 ), herd size ( β = 4.276, 7.197; p = 0.001 ), farm size ( β = - 1.734, .048; p = . 176 ), the police ( β = - . 912, 4.582; p = . 043 ), and village leaders ( β = - . 122, .885; p = . 012 ) were the most potent predictors of causes of conflicts. The study found no support for demographic variables, like age, sex, marital status, income, duration of residence, and distance to resource base. The study recommends population growth control and strengthening of local institutions and recommends local communities to sustain management of natural resources base in the area.